Quick Response in Manufacturer-Retailer Channels - Iyer, Ananth. V.; Bergen, Mark E. (Management Science, 1997)
Quick Response (QR) is a movement in the apparel industry to shorten lead time. Under QR, the retailer has the ability to adjust orders based on better demand information. We study how a manufacturer-retailer channel impacts choices of production and marketing variables under QR in the apparel industry. Specifically, we build formal models of the inventory decisions of manufacturers and retailers both before and after QR. Our models allow us to address who wins and who loses under QR, and suggest actions such as service level, wholesale price and volume commitments that can be used to make QR profitable for both members of the channel, i.e., Pareto improving. Detailed discussions with a major retailer, and information from industry sources provide supporting evidence for the structure and conclusions of the model.